â€œSEASIDEâ€ SEBUAH ALTERNATIF KONSEP PERMUKIMAN - Setiawan, Altim; Sirajuddin, Zainal (MEKTEK, 2006)
This article represents literature study about a town design model on Florida's northwest coats. The idea of Seaside is started with the notion of reviving Northwest Florida's building tradition and involvement of Andreas Duany designer urban and Elizabeth Plater-Zyberk with new urbanismn concepts and also seaside development of Robert Davis in Seaside area. Writer also tries to study excess from sideside design and aspect that is left behind in this design model